Nonpathogenesis of Simian Immunodeficiency Virus Infection Is Associated with Reduced Inflammation and Recruitment of Plasmacytoid Dendritic Cells to Lymph Nodes, Not to Lack of an Interferon Type I Response, during the Acute Phase - Campillo-Gimenez, Laure (American Society for Microbiology (ASM), 2010)
Divergent Toll-like receptor 7 (TLR7) and TLR9 signaling has been proposed to distinguish pathogenic from nonpathogenic simian immunodeficiency virus infection in primate models. We demonstrate here that increased expression of type I interferon in pathogenic rhesus macaques compared to nonpathogenic African green monkeys was associated with the recruitment of plasmacytoid dendritic cells in the lymph nodes and the presence of an inflammatory environment early after infection, instead of a difference in the TLR7/9 response.